Solar retinopathy with interesting imaging findings. A case report - Oh, KL; Wong, HS; Safinaz Mohd Khialdin,; Lakana K,; Hazlita Mohd Isa, (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2016)
Solar retinopathy is an injury of the retinal photoreceptors due to excessive exposure to the solar radiation. Diagnosis of the disease is challenging and requires combination of a detailed history and imaging modalities. This case report focuses on a 55-year-old fruit picker with an irreversible central scotoma of the right eye. A diagnosis of solar retinopathy was made based on history but mainly by several imaging modalities, such as optical coherence tomography (OCT), infrared (IF)imaging of the fundus and fundus autofluorescence (FAF). Electroretinogram (ERG)showed flattened and reduced waves in both scotopic and photopic response. Fundus angiography (FA) revealed no obvious telangectatic vessels. In conclusion, solar retinopathy is a disease where multimodal imaging may play an important role in the diagnosis. The condition may be irreversible thus advocating protective eyewear is mandatory in patients who are chronically exposed to the sun.